Analisis Kelayakan Bahan Ajar Kearsipan Berbasis Kurikulum 2013 Ditinjau Dari Pemanfaatan Guru Dan Siswa Kelas X Administrasi Perkantoran Sekolah Menengah Kejuruan (SMK) Negeri 6 Surakarta - Ervinda Kusumaningtyas; Andre N. Rahmanto; Jumiyanto Widodo (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2017)
This research is aimed to know about: (1) the appropriateness of Modul Kearsipan based on 2013 curriculum seen by the utilization of teachers and students of the tenth grade of Office Administration of Vocational High School (SMK) Negeri 6 Surakarta; (2) the problems of the teachers and the students in utilizing the Modul Kearsipan based on 2013 curriculum which implicated in the Vocational High School (SMK) Negeri 6 Surakarta; (3) the solutions to solve the problems of the teachers and the students in utilizing the Modul Kearsipan based on 2013 curriculum which implicated in the Vocational High School (SMK) Negeri 6 Surakarta. This research used qualitative method with the case study as the research approach. The informants in this research are the teachers of Archival subject, the productive teachers of Office Administration, the tenth grade students of Office Administration. The data collection used interactive analysis where the activities involved were data reduction, data display, and also conclusion drawing and verification. The data validity was done by using triangulation method and source. From the finding of the research, it can be concluded that (1) the appropriateness of the Modul Kearsipan based on 2013 curriculum seen by the utilization of the teachers and the students consisted of: (a) Modul Kearsipan of the tenth grade students of the second semester for SMK based on 2013 curriculum is appropriate with all of the indicators of the content appropriateness of the module. (b) Modul Kearsipan of X of the second semester for SMK based on 2013 curriculum is appropriate with all of the indicators of language appropriateness. (c) Modul Kearsipan of X of the second semester for SMK based on 2013 curriculum is not yet completing the two indicators of display appropriateness, however it has completed the three indicators of display appropriateness. (d) Modul Kearsipan of the second semester for SMK based on 2013 curriculum is not yet completing one of the indicator of graphic appropriateness, however it has completed the three indicator of the rest. (2) The problems faced are: (a) the less of practice and exercises from the module, (b) the type of the module is less organized, (c) the less of the examples from the electronic archival material, (d) the goal of the learning is not displayed, (e) the utilization of the students on the module. (3) The solutions are done as follows: (a) adding the exercises for students’ practice, (b) retyping of the unorganized module, (c) adding the materials and examples for electronic archival, (d) displaying the goal of the learning in the module, (e) the utilization of the module through the facility of the library.